DESAIN DAN PERANCANGAN APLIKASI JEMPUT SAMPAH ONLINE DESA REJOSARI MENGGUNAKAN AGILE DEVELOPMENT - Sony Panca Budiarto; Mohamad Dedi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
Garbage is a used item of human need. Garbage hurts the environment and health. Realized or not every day there is a buildup of organic waste or non-organic waste. The problem of garbage is not only in the city, in Rejosari Village Banyuwangi Regency, but the reach of modern shops selling the needs of people packed plastic, cloth, cans, beverage bottles, iron, glass and so on that are also classified in non-organic waste. The amount of land is empty, there is no temporary landfill, the garbage is disembarrassed and then burned even the garbage is swept into the river. Waste Management should be done comprehensively from upstream to downstream starting from the village. This research is planned for an integrated waste management system of technology and information. With this app people can make money by selling garbage through the app, no need to come to the garbage bank, there will be garbage collectors who come to buy their garbage. People save garbage or exchange garbage for handicrafts or necessities. The application displays the type of garbage that has a selling value, craft products, or staples needs that can be exchanged for garbage. Collectors who buy garbage must sell or save garbage to the Garbage Bank. Applications are developed by the Agile Development method with XP (Extreme Programming). Testing using the black-box testing method, the results went well as planned.